The Correlation Study Between Seminal Fluid Enzymes and Effects on Men’s Fertility - AL-Mansouri, Nibras Abbas; Ali Rzoqy , Hussain; Mohammed J. I, Al-Shammari; A. Dabbi, Mohammed; Hassanin Hashim, Noor (Clinical Medicine And Health Research Journal, 2024)
Objective: By analyzing the relationship between ALP, GOT, and LDH action within the seminal plasma of fruitless men and comparing it with ripe men, this study aimed to investigate the physiological conditions that remain unexplained in most cases. Methods: This study collected forty-four semen tests from normospermic men and 20 tests from fertile men, after a period of forbearance (3-5 days). The tests were analyzed within the Babylon Maternity and Children research facility and private research facilities, from January 2024 to April 2024. Results: The results indicated that ALP and AST activity had a negative correlation in both fertile (r = - 0.123) and normospermic men (r = - 0.038). Similarly, ALP and LDH activity had a negative correlation in fertile men (r = -0.334), but a positive correlation that was not significant (P˃0.05) in normospermic men (r= 0.128). Moreover, the results showed that AST and LDH activity positively correlated in both normospermic (r=0.058) and fertile men (r=0.242). Conclusion: The study hypothesized that normal semen components and gland secretory ability may be indicated by ALP, AST, and LDH activity. The levels of ALP, AST, and LDH activity in males who were fertile and those who were not showed any discernible differences.